Development of Structure-Switching Aptamers for Kanamycin Detection Based on Fluorescence Resonance Energy Transfer - Ma, Xinyue; Qiao, Shangna; Sun, Hongjing; Su, Ruifang; Sun, Chunyan; Zhang, Mingdi (Frontiers in Chemistry, 2019)
The structure-switching aptamers are designed for the simple and rapid detection of kanamycin based on the signal transduction principle of fluorescence resonance energy transfer (FRET). The structure switch is composed of kanamycin-binding aptamers and the complementary strands, respectively labeled with fluorophore and quencher, denoted as FDNA and QDNA. In the absence of kanamycin, FDNA and QDNA form the double helix structure through the complementary pairing of bases. The fluorophore and the quencher are brought into close proximity, which results in the fluorescence quenching because of the FRET mechanism. In the presence of kanamycin, the FDNA specifically bind to the target due to the high affinity of aptamers, and the QDNA are dissociated. The specific recognition between aptamers and kanamycin will obstruct the formation of structure switch and reduce the efficiency of FRET between FDNA and QDNA, thus leading to the fluorescence enhancement. Therefore, based on the structure-switching aptamers, a simple fluorescent assay for rapid detection of kanamycin was developed. Under optimal conditions，there was a good linear relationship between kanamycin concentration and the fluorescence signal recovery. The linear range of this method in milk samples was 100 - 600 nM with the detection limit of 13.52 nM (3σ), which is well below the maximum residue limit of kanamycin in milk. This method shows excellent selectivity for kanamycin over the other common antibiotics. The structure-switching aptamers have been successfully applied to the detection of kanamycin spiked in milk samples with the satisfying recoveries between 101.3% and 109.1%, which is well consistent with the results from LC-MS/MS. Due to the outstanding advantages of facile operation, rapid detection, high sensitivity, excellent specificity, and low cost, the application and extension of this strategy for rapid determination of antibiotics in food samples may greatly improve the efficiency in food safety and quality supervision.